Grafting epoxidized natural rubber on hydroxyethyl cellulose/polyvinyl alcohol nanofiber: Morphology and chemical composition - Tong, Hui Shan; Farah Hanani, Zulkifli; Siti Maznah, Kabeb (John Wiley & Sons, Inc., 2026)
The growing wound care market and global waste production increase the demand for biodegradable biomaterials. Epoxidized natural rubber has suitable properties such as biocompatibility, high mechanical strength, flexibility, and elasticity to serve as a biomaterial in the production of cellular scaffolds, wound dressings, transdermal drug delivery patches, and sustained drug delivery system components. To further enhance its suitability as a biomaterial, epoxidized natural rubber is graft copolymerized with hydroxyethyl cellulose and polyvinyl alcohol, which are both highly biocompatible and non-cytotoxic materials. The grafted material is then electrospun to mimic the extracellular matrix of skin, which can potentially improve the healing abilities of the nanofiber. The epoxidation of natural rubber is confirmed through Proton Nuclear Magnetic Resonance (1 H NMR), while a more closely packed, orderly structure and higher carbon to oxygen ratio is seen through Field Emission Scanning Electron Microscopy with Energy Dispersive X-Ray Spectroscopy (FESEM-EDX), along with additional functional groups depicted through Attenuated Total Reflectance Fourier Transform Infrared Spectroscopy (ATR-FTIR) with the addition of epoxidized natural rubber. In conclusion, the morphology and chemical composition of epoxidized natural rubber-grafted-hydroxyethyl cellulose (ENR-g-HEC) nanofibers are suitable to be used as a biomaterial in biomedical applications.